Design and analysis of slotted core photonic crystal fiber for gas sensing application - Paul, Bikash Kumar; Rajesh, E.; Asaduzzaman, Sayed; Islam, Md. Shadidul; Ahmed, Kawsar; Amiri, Iraj Sadegh; Zakaria, Rozalina (Elsevier, 2018)
In this paper, a slotted core photonic crystal fiber (PCF) has been designed. A rigorous numerical investigation has been done over the wider range of the wavelength from 1.30 µm to 2.0 µm near inferred region (IR). By employing full vectorial finite element method (FV-FEM) having completely circular anisotropic perfectly matched layer (C-PML) different optical parameter such as nonlinearity, confinement loss, sensitivity, beat length, V-parameter and splice loss of the modeled PCF have been uncovered. The investigated upshot testifies that the birefringence gained at the order of 10 −2 . Nevertheless, the proposed fiber experienced with the lower order (1.26 × 10 −5 dB/m) of confinement loss with a higher order of nonlinearity 54.33 W −1 km −1 at simultaneously at the operating optical wavelength λ = 1.33 µm. Moreover, the impacts of the geometric parameters have been turned on birefringence, nonlinearity and confinement losses which are also analyzed in detail. The proposed PCF model with investigated results provides stronger evidence that, the structure will play a substantial role in the area of optical waveguides as well as optical devices or instrumentations.